Análise do ensaio de compressão de um compósito formado pelo subproduto do processo de dessulfurização dos gases de combustão e espuma vinílica acetinada - (:unkn) unknown (Universidade Federal do Pampa, 2016)
With the population increasing the demand for electricity grows in the same range, as the human use of more electrical appliances in their daily lives. Consequently it makes the industry responsible for electricity generation in Brazil grow in the same proportion. Part of this power generation is performed by thermal power plants to coal. However, these plants generate waste, such as waste from the desulphurization process of the flue gases. The need to seek a technical destination and economically viable waste from the desulfurization process in power generation in a power plant is intended to give a utility for this residual compound seeking help with social and environmental needs of the region. This residue consists of sulfate and calcium sulfite (CaSO4 and CaSO3), inert (ash residues nonreactive) and other reaction products such as calcium carbonate and calcium hydroxide (CaCO3, Ca(OH)2), between others. This work aims to study the characteristics of a composite from the mixture of this residue (calcium sulphate) with ground satin vinyl (EVA) foam, mainly from the footwear industry, which is also a waste from the industrial process. From this composite will be produced test specimens so that it can be characterized by mechanical compression tests, besides the performance of morphological analysis. All tests shall be carried out in compliance with the ABNT NBR 12129 standard for plaster for civil construction, as well as for the analysis of the results. As a result of the development and analysis of the tests, it is expected to obtain relevant information to verify if it is possible and feasible the development of a low cost composite for use in construction, contributing to the recycling of these two industrial wastes.
Keywords: Engenharia; Engenharia de produção; NBR 12129; ABNT; Compósito; Sulfato de cálcio; Espuma vinílica acetinada; CNPQ::ENGENHARIAS